ANKAphase: software for single‐distance phase retrieval from inline X‐ray phase‐contrast radiographs. Erratum. (26th December 2012) - Weitkamp, T.; Haas, D.; Wegrzynek, D.; Rack, A.
<x xml:space="preserve">Abstract</x> An equation in the paper by Weitkamp et al. [(2011), J.Synchrotron Rad.18, 617629] is corrected.